The Correlation between Fatigue and Quality of Life on Knee Osteoarthritis Patient at RSD dr. Soebandi Jember - Yuli Hermansyah; Marwah Pradani Ridlo; Desie Dwi Wisudanti (Journal of Agromedicine and Medical Sciences, 2022)
Osteoarthritis (OA) is a form of chronic arthritis that mainly attacks the knee joint. The prevalence of knee OA in Indonesia, especially in East Java, is around 27% which is relatively high. Therefore, this study aims to determine the correlation between fatigue and quality of life from knee OA patients at RSD dr. Soebandi Jember. The methodology uses in this study is the analytical observational method with a cross-sectional survey as the research design. For the data, this study uses primary and secondary data. The primary data was obtained through online interviews by phone using a questionnaire instrument, namely Fatigue Assessment Scale (FAS) and World Health Organization Quality of Life (WHOQOL) – BREF. Then, the secondary data was obtained from the medical records of knee OA patients who were undergoing treatment at the RSD dr. Soebandi Jember in the period January 2019 to December 2020. The results of this study showed that the p-value of fatigue with quality of life domain 1 (physical health) was 0.042, domain 2 (psychological) was 0.087, domain 3 (social) was 0.221, and domain 4 (environmental) was 0.426. Therefore, this study concludes that there is a weak relationship between fatigue and quality of life on domain 1 (physical health), with a correlation coefficient of 0.373. Also, there is no relationship between fatigue and quality of life on domain 2 (psychological), domain 3 (social), and domain 4 (environmental) in knee OA patients at RSD dr. Soebandi Jember. Keywords: knee OA, fatigue, quality of life